AWARD : for the Teaming Project Excelsior - Hadjimitsis, Diofantos G. (My University, 2026)
24th of September 2019 in Brussels. Award for Diofantos Hadjimitsis as Coordinator: During the event Jean-Eric Paquet, Director-General for Research and Innovation congratulated the 14 Teaming projects winners on this outstanding initiative and their contribution to bridging the research and innovation divide in Europe. Teaming projects under the Horizon 2020 Widening Programme aim at setting up and developing new ‘centres of excellence’ in low R&I performing Member States.Together with the project coordinators, Jean-Eric signed the certificates acknowledging that each of these 14 projects will establish a Centre of Excellence in their countries and receive for that a corresponding phase 2 Teaming grant of around 15 million euros. The signature of the certificates/award was followed by a shared meeting gathering the responsible units for policy development in DG RTD and for project implementation in REA. Both Heads of Units, Magda de Carli and Ales Fiala, as well as the Director of REA Marc Tachelet addressed the audience.
Keywords: Sciences